2019
DOI: 10.1002/jcp.28366
|View full text |Cite
|
Sign up to set email alerts
|

AZGP1 is androgen responsive and involved in AR‐induced prostate cancer cell proliferation and metastasis

Abstract: Alpha‐2‐glycoprotein 1, zinc‐binding (AZGP1), known as zinc‐alpha‐2‐glycoprotein (ZAG), is a multifunctional secretory glycoprotein and relevant to cancer metastasis. Little is known regarding the underlying mechanisms of AZGP1 in prostate cancer (PCa). In the present study, we report that AZGP1 is an androgen‐responsive gene, which is involved in AR‐induced PCa cell proliferation and metastasis. In clinical specimens, the expression of AZGP1 in PCa tissues is markedly higher than that in adjacent normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
4
20
2
Order By: Relevance
“…Six genes were incorporated into this model, consisting of AZGP1, IGF2BP2, MEX3A, NUDT16, NUP153, and USB1. A recent research proved that AZGP1 is an AR target gene and is involved in androgen/AR axis-mediated cell proliferation and metastasis in primary PCa ( 28 ). Meanwhile the six-gene model revealed that high expression of AZGP1 was negatively associated with prognosis in thyroid cancer, so it might also play a critical role in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Six genes were incorporated into this model, consisting of AZGP1, IGF2BP2, MEX3A, NUDT16, NUP153, and USB1. A recent research proved that AZGP1 is an AR target gene and is involved in androgen/AR axis-mediated cell proliferation and metastasis in primary PCa ( 28 ). Meanwhile the six-gene model revealed that high expression of AZGP1 was negatively associated with prognosis in thyroid cancer, so it might also play a critical role in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated involvement of the AR target gene—alpha-2-glycoprotein 1, zinc-binding ( AZGP1 )—in induction of PCa proliferation and metastasis. The authors revealed that AR signaling was responsible for upregulation of AZGP1 and enhancement of cell proliferation in vitro and in vivo through the androgen/AR axis [92].…”
Section: Androgen Receptor (Ar) and Pcamentioning
confidence: 99%
“…Analyses of the Hallmark gene sets revealed androgen response genes were negatively and peroxisome genes positively enriched, respectively, suggesting that PGC1α expression represses AR signaling and enhances the activity of the peroxisome. AR target genes notably associated with energy production were repressed, including the putative tumor suppressor hydroxyprostaglandin dehydrogenase ( HPGD ) 75 , as well as Acyl-CoA synthetase long chain family member 3 (ACSL3) 76 and Alpha-2-glycoprotein 1, zinc-binding ( AZGP1 ) 77 . Up-regulated peroxisome genes included retinoic acid anabolizing enzyme, Dehydrogenase/Reductase 3 ( DHRS3 ) 78 , and the steroid catabolizing enzyme UDP Glucuronosyltransferase Family 2 Member B17 ( UGT2B17 ) 79 .…”
Section: Resultsmentioning
confidence: 99%